Metabotropic glutamate receptor 4-mediated glutamatergic signaling reshapes the tumor microenvironment by regulating dendritic cell maturation - Xiaoman Ju; Eva Maria Putz; Yaqi Liu; Dongchen Yuan; Guowei Sun; Stephane Koda; Zhuo Fu; Simin Shao; Chunrong Tong; Biping Deng; Jing Hu; Juming Yan (Nature Communications)
Abstract Metabotropic glutamate receptor 4 (mGluR4, encoded by Grm4), is a neurotransmitter receptor, known to play roles in tumor progression and immune modulation through the nervous system. Here we show that mGluR4 may regulate immune responses in the tumor microenvironment (TME) also via non-neuronal mechanisms. We observe that dendritic cells (DC) from mGluR4-deficient mice display enhanced migration, maturation and antigen-presentation capacity, which promote T cell and NK cell responses against tumor cells. Tumor growth and metastases are suppressed in Grm4 -/- mice in different preclinical tumor models, including orthotopic liver cancer, subcutaneous melanoma, colorectal tumors, and fibrosarcoma. We show that the tumor suppressive effect of Grm4-deficiency requires host immunity, in particular CD8+ T cells, NK cells, and IFNγ, but independent of the nervous system. Single-cell RNA-sequencing and ex vivo assays show changes in the composition and functional state of the immune TME. Mechanistically, mGluR4 suppresses the adenyl cyclase/PKA signaling pathway, leading to metabolic reprogramming of DCs. Importantly, adoptive transfer of DCs pretreated with the AC agonist forskolin therapeutically suppressed tumor growth in an orthotopic liver cancer model. Our study thus demonstrates that mGluR4 is a checkpoint for DC maturation and that mGluR4 may serve as an immunotherapeutic target.